Exoplanet Two-Square Degree Survey With SAO RAS Robotic Facilities - Yakovlev, Oleg Ya.; Valeev, Azamat F.; Valyavin, Gennady G.; Tavrov, Alexander V.; Aitov, Vitaly N.; Mitiani, Guram Sh.; Korablev, Oleg I.; Galazutdinov, Gazinur A.; Beskin, Grigory M.; Emelianov, Eduard V.; Fatkhullin, Timur A.; Vlasyuk, Valery V.; et al. (Frontiers in Astronomy and Space Sciences, 2022)
The 0.5-m robotic telescopes located at the Special Astrophysical Observatory of the Russian Academy of Sciences were used for monitoring two square degrees of the sky with the aim of detecting new exoplanets. A dimming of the visible brightness is expected due to exoplanets transiting their parent stars. About 25000 of raw images of stars taken in the period between August 2020 and January 2021 were analyzed and the light curves of about 30000 stars on a half-year timescale were constructed. Five newly discovered exoplanet candidates are being investigated to determine their transit event parameters. Also we present the light curves of dozens of binary stars.